OP0192 Early Treatment-Naive Rheumatoid Arthritis (RA) is Characterised by Qualitative Changes of the INKT Regulatory Cell Repertoire. (23rd January 2014) - Mansour, S.; Tocheva, A.; Edwards, M.; Goulston, L.; Platten, H.; Parsons, C.; Edwards, C.; Cooper, C.; Gadola, S. D.
Abstract : Background: Innate mechanisms of inflammation control are central to the pathogenesis of autoimmune diseases (AID), including RA. Invariant Natural Killer T cells (iNKT) are a highly conserved T-cell subset with key roles in immune tolerance. iNKT-targeting therapeutic approaches are highly effective in animal models, but translation to human AID has not yet succeeded. Objectives: We have previously defined the human iNKT repertoire according to the clonal distribution of high- and low-affinity iNKT T-cell receptors 1 . Here we have investigated the iNKT repertoire with regard to function and T-cell receptor affinity in early Rheumatoid Arthritis. Methods: 100 early RA patients and 50 matched healthy people were included. Multiple iNKT clones from patients and controls were generated and analysed for TCR affinity to the restriction element human CD1d by using different CD1d/ligand-tetramers; Clones were analysed for cytokine secretion in response to CD1d/antigen and mitogen stimulation; iNKT frequency and CD1d expression on antigen presenting cells were determined by FACS; in vitro expansion of iNKT cells to antigen-pulsed autologous monocytes and recombinant CD1d/antigen coated beads was compared to differentiate inherent iNKT cell defects from defects in antigen presentation. Results: The clonal repertoire of iNKT cells in healthy controls shows a broad distribution with regard to iNKT receptor affinity for CD1d. In contrast, the repertoire is highly significantly shifted towards lower-affinity iNKT clones in age-matched early RA. This shift correlates with DAS28. Analysis of untreated vs treated early RA patients shows that the iNKT repertoire is "restored to normal" in the DMARD group, and this correlates with DAS28. CD1d expression on antigen-presenting cells was not different between groups. iNKT cells in all early RA patients exhibited a bias in cytokine secretion towards Th1 cytokines, independent of CD1 antigen processing. Conclusions: This is the first demonstration of changes in a T-cell compartment based on TCR-affinity during disease. The repertoire of iNKT cells in blood is significantly changed in early treatment-naive RA, with loss of higher-affinity iNKT TCR bearing cells that may have key roles in immunological tolerance. Our findings are relevant for all iNKT cell targeting approaches in humans, including those designed for restoring tolerance in AID, and also those designed for promoting inflammation in cancer or infection. References: Matulis G, et al. PLoS Biol. 2010; 22;8(6):e1000402. doi: 10.1371/journal.pbio.1000402. Acknowledgements: Funded by Arthritis Research UK (to SDG) Disclosure of Interest: None Declared